A Synthetic test of rhythm - Jayanthi Ray (Journal of All India Institute of Speech and Hearing, 1970)
Suprasegmentals are properties of speech that have a domain larger than a single element. For being analogous to, superficial decoration, suprasegmentalsor prosody consisting of stress, rhythm, intonation & juncture, functions as the foundation or structural support for the organisation of speech communication.Of these, rhythm is intrinsic & critical in both production & perception of speech. Several studies have been conducted in the past to gain a knowledge of thedevelopment of speech rhythm in children. However, this topic is not yet understood & there is a pressing need to conduct research in this area, in order to use itclinically. In this context the present study was aimed to highlight the developmental trend of rhythm in children & develop a synthetic test of rhythm.